ANTESEDEN KESETIAAN PASIEN DALAM KONTEKS PEMASARAN HUBUNGAN - Aslam Al Hussaini; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
his study aims to examine patient loyalty which is influenced by relationship marketing within the hospital institution. Data were obtained through quisionnares that were distributed directly to PKU Muhammadiyah Surakarta hospital patient. The sample of this study amounted to 200. The sampling technique used pur posive sampling technique. Hypothesis testing using SEM (Structural Equation Modeling). The result in this study indicate that the quality of the relationship has a significant effect on patient loyalty. Satisfaction has no significant effect on patient loyalty. Trust has no significant effect on patient loyalty. Commitment has significant effect on patient loyalty. The relationship benefits have a significant effect on the quality of the relationship. The relationship benefits have a significant effect on satisfaction. The relationshi p benefits have a significant effect on trust. The relationship benefits have a significant effect on commitment.